Effect of Investment Knowledge, Return Perception, and Investment Motivation on Gold Investment Interest in Dana Digital Wallet Application in Islamic Business Perspective (Study on Gen Z in Bandar Lampung City) - Ricky Febriansyah; Suhendar; Liya Ermawati (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of investment knowledge, perception of Return, and investment motivation on gold investment interest through the DANA digital wallet application on Generation Z in Bandar Lampung City. The research method used is quantitative with survey techniques through the distribution of questionnaires to respondents who meet the criteria. Data analysis technique is done using Partial Least Square (PLS). The results showed that investment knowledge variables have a positive and significant influence on investment interest, indicating that a good understanding of financial instruments can improve investment decisions. The perception of Return has also been shown to have a positive and significant influence, which indicates that the view of stable profits encourages investment interest in digital gold. In addition, investment motivation also has a positive and significant effect on investment interest, where psychological motivation and financial goals encourage consistency in investment behavior. In the perspective of Behavioral Finance, these three variables show the psychological contribution, risk perception, and individual confidence in investment instruments. Furthermore, in the perspective of Islamic business, digital gold investment through a platform that is transparent and free of speculation is considered halal and can maintain the blessing of wealth. Thus, this study confirms that internal factors and financial perceptions play an important role in shaping the interest of digital gold investment in Gen Z in the current era of financial technology development. Purpose-this study was conducted to understand the effect of investment knowledge, perception of Return, and investment motivation on gold investment interest through the DANA digital wallet application on Generation Z in Bandar Lampung City. The focus of the study is directed to efforts to identify how much psychological factors, financial perceptions, and investment literacy levels are able to shape investment decisions in the digital age. In addition, this study aims to provide an overview of the investment behavior of the younger generation in the perspective of Islamic business, which emphasizes the principles of halal, transparency, and productive management of property. Thus, the results of this study are expected to contribute to the development of Sharia financial literacy and increase interest in digital gold investments that are safe, easily accessible, and in accordance with the muamalah principle. The novelties of this study lies in the use of a combination of investment knowledge variables, perception of Return, and investment motivation simultaneously in analyzing gold investment interest through the DANA digital wallet application in Gen Z in Bandar Lampung City in the perspective of Islamic Business. Previous research has generally focused on conventional investments, marketplace platforms, or other instruments without considering Sharia aspects and the behavior of young investors towards digital gold. In addition, the object of research that is centered on digital wallet users as an investment medium makes this study relevant to the development of modern financial technology. The location and period of the study also provide an updated overview of the investment trends of the younger generation after the increase in financial digitization